2022
DOI: 10.1177/03635465221131005
|View full text |Cite
|
Sign up to set email alerts
|

Meniscal Extrusion Measurements After Posterior Medial Meniscus Root Tears: A Systematic Review and Meta-analysis

Abstract: Background: Meniscal extrusion has become increasingly utilized when evaluating meniscus root abnormalities. However, no consensus definition or approach exists on how to measure extrusion. Purpose/Hypothesis: The purpose of this study was to evaluate the extent of heterogeneity in meniscal extrusion measurement techniques and reported extrusion values in knees with posterior medial meniscus root tears (PMMRTs). We hypothesized that meniscal extrusion measurement techniques would vary considerably throughout r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 71 publications
2
10
0
Order By: Relevance
“…With respect to measurement techniques, most available studies report using a reference line representing 0 mm of ME based on the location of only the medial tibial plateau, rather than a line connecting the vertices of the tibial and femoral cortices at the joint line. 11 , 15 The latter approach is difficult to reproduce, given that the femoral condyle is convex; therefore, identifying the vertex where the joint line begins on the femur is challenging to identify. In turn, an accurate reference line becomes challenging to consistently create.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to measurement techniques, most available studies report using a reference line representing 0 mm of ME based on the location of only the medial tibial plateau, rather than a line connecting the vertices of the tibial and femoral cortices at the joint line. 11 , 15 The latter approach is difficult to reproduce, given that the femoral condyle is convex; therefore, identifying the vertex where the joint line begins on the femur is challenging to identify. In turn, an accurate reference line becomes challenging to consistently create.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis demonstrated that ME pooled from all patients with PMMRTs was 3.2 ± 2.0 mm—a wide range. 11 In addition, they also found that authors measured ME at various landmarks, including the medial collateral ligament in 38% of studies, the midpoint of the anterior−posterior length of the medial meniscus in 23% of studies, the middle of the medial femoral condyle in 19% of studies, and more. Given its low absolute measured values in the order of millimeters, ME is a fragile metric and requires a systematic and reproducible measurement technique so quantitative values can be meaningful.…”
mentioning
confidence: 96%
“…Abnormal medial meniscus extrusion is deined as protrusion of the body of the medial meniscus beyond the tibial plateau [15]. In literature the presence of a meniscal lesion is often associated with meniscal extrusion [7,8,23]. Due to the anatomy of the medial meniscus, various lesions are described as more or less responsible for meniscal extrusion [9,11,18].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the definition of MME was based on the extrusion of the medial meniscus ≥ 3 mm [16, 50] and meniscal extrusion score ≥ 1 (0 = no extrusion, 1 = partial meniscal extrusion, and 2 = complete meniscal extrusion) on the coronal plane of MRI [38]. The inclusion criteria for this study were as follows: (1) articles reporting at least one factor associated with concomitant MME with OA or MMT; (2) study design included cross‐sectional, case–control, prospective or retrospective, and cohort studies; (3) study sample size was > 10 patients.…”
Section: Methodsmentioning
confidence: 99%
“…The medial meniscus on the tibial plateau serves an important function in the knee joint by facilitating shock absorption, load distribution, and reducing friction, thereby enhancing knee stability [9]. Medial meniscus extrusion (MME) refers to the protrusion of the medial meniscus beyond the tibial edge by more than 3 mm, leading to compromised hoop strain [16]. Biomechanical studies have demonstrated that MME reduces the tibiofemoral contact area and directly affects the ability of joints to adapt to load, increasing the risk of osteoarthritis (OA) [12].…”
Section: Introductionmentioning
confidence: 99%